Pengaruh Price Earning Ratio, Price Book Value dan Debt to Equity Ratio Terhadap Harga Saham pada PT Indocement Tunggal Perkasa Tbk - Fatmawati, Reny; Muniarty, Puji (BanKu: Jurnal Perbankan dan Keuangan, 2023)
This study aims to determine the effect of Price Earning Ratio, Price Book Value and Debt Equity To Ratio on srock prices at PT. Indocement Tunggal Perkasa Tbk. This type of research uses an associative method, with research samples for 6 years from 2016-2021 accessed through the official website Â www.idx.co.id. Data collection techniques use the Classical Assumption Test, Multiple Linear Regression Analysis, Partial Test (T Test) and Simultaneous Test (F Test). The result showed that PER had no partial significant effect on stock prices, PBV had no partial signuficant on stock prices, DER had no partial significant effect on stock prices and PER, PBV and DER had no simultaneous significant effect on stock prices.